202 AMPK Activation Partially Restores the Anti-Contractile Effect of Perivascular Adipose Tissue in Female Offspring of Obese Rats. (3rd June 2016) - Zaborska, Karolina; Edwards, Gillian; Austin, Clare; Wareing, Mark
Abstract : Introduction: Maternal obesity programmes offspring to develop obesity and associated cardiovascular disease. Perivascular adipose tissue (PVAT) exerts an anti-contractile effect in healthy blood vessels; an effect lost in male offspring of obese dams. However, the mechanism by which maternal obesity programmes PVAT dysfunction in offspring remains unknown. Methods: Six week old female Sprague-Dawley rats were fed a control (10% fat) or 45% fat obesogenic diet (HFD) for 12 weeks before mating; during pregnancy and lactation. At weaning, female offspring were provided with the control diet until sacrifice at either 12 (12 wo) or 24 (24 wo) weeks of age. PVAT-denuded mesenteric arteries from pups, with or without exogenous PVAT, were mounted on a wire myograph and concentration-response curves were constructed to thromboxane A2 receptor agonist U46619 (10 nM-3 µM) ± 10 µM A769662, an activator of AMP-activated protein kinase (AMPK) ± glucosamine (an O-GlcNAcylator). Western blotting was used to asses protein expression in PVAT stimulated with or without glucosamine. Results: Body weight, insulin levels and blood pressure were increased in HFD dams and their 12wo and 24 wo offspring compared to age-matched controls. Without PVAT, vessel contractions to U46619 were reduced in 12 wo offspring of HFD dams, effects mimicked in control arteries by pre-incubation with 10 mM glucosamine. PVAT from control, but not from HFD offspring, exerted an anti-contractile effect on the corresponding PVAT-denuded arteries at both ages. Pre-incubation of control PVAT with glucosamine diminished the anti-contractile effect at both ages. PVAT from HFD offspring pre-incubated with glucosamine had no effect on PVAT-denuded vessels but simultaneous AMPK activation within PVAT partially restored anti-contractile capability at both ages. Protein O-GlcNAcylation expression was increased in HFD PVAT and control PVAT incubated with glucosamine, whereas AMPK expression was decreased. Conclusions: The enhanced protein O-GlcNAcylation and decreased AMPK expression in HFD PVAT may underlie the reduced anti-contractile effect of PVAT in female offspring of obese dams. Nevertheless, simultaneous AMPK activation within HFD PVAT partially restored the anti-contractile effects of PVAT.